Rapid Urban Expansion and Its Implications on Geomorphology: A Remote Sensing and GIS Based Study. (20th October 2014) - Mohapatra, S. N.; Pani, Padmini; Sharma, Monika
Abstract : Topography, vegetation, climate, water table, and even the anthropogenic activities all are affected by urban growth through diverse mechanisms. The present study focuses on the implications of urban expansion on geomorphology in the historical city of Gwalior in central India. The expansion of urban area has been quantified by deriving data for four decades (1972–2013) from the Landsat images. The results show that the urban built-up area has increased by 08.48 sq. km during the first eighteen years (1972–1990) which has increased to 16.28 sq. km during the next sixteen years (1990–2006). The built-up area has gone up to 23.19 sq. km in the next seven years (2006–2013). Overall during the last 40 years the growth of the urban built-up is nearly three times of the built-up areas in 1972. The average decadal growth rate of population is 27.28 percent while that of built-up land is 36.29 percent. The construction activities have affected important geomorphic features such pediplain, buried pediplain, residual hills, and denudational hills. It was concluded that, instead of shortsighted urban development, proper measures should be taken in accordance with scientific planning for the urban expansion of the city in the future.